1972
DOI: 10.1139/v72-374
|View full text |Cite
|
Sign up to set email alerts
|

Self Association of Folic Acid in Aqueous Solution by Proton Magnetic Resonance

Abstract: Proton magnetic resonance experiments on the disodium salt of folic acid in aqueous solutions (pD 7.1) indicate that the folate ion exists in an unfolded, extended conformation in solution. However, based on a temperature and concentration dependence of the proton chemical shifts, folate ions are involved in intermolecular association consisting of a vertical stacking interaction. A stacking model is proposed for the association with the hydrophilic ends of the molecule alternating in orientation with respect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

1975
1975
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 15 publications
2
11
0
Order By: Relevance
“…b The N4-F7 distance is based on a few ILOE cross-peaks observed at longer mixing times. formation of large aggregates, which has been described previously (20,21). Lam and Kotowycz (20) suggested that the aggregates involve stacking interactions between approximately coplanar p-aminobenzoyl and pterin ring systems, such that the pterin ring of one folate is in close proximity with the p-aminbenzoyl rings of the adjacent folate molecules, and with alternate anionic glutamyl groups facing in opposite directions.…”
Section: Resultssupporting
confidence: 66%
“…b The N4-F7 distance is based on a few ILOE cross-peaks observed at longer mixing times. formation of large aggregates, which has been described previously (20,21). Lam and Kotowycz (20) suggested that the aggregates involve stacking interactions between approximately coplanar p-aminobenzoyl and pterin ring systems, such that the pterin ring of one folate is in close proximity with the p-aminbenzoyl rings of the adjacent folate molecules, and with alternate anionic glutamyl groups facing in opposite directions.…”
Section: Resultssupporting
confidence: 66%
“…This may be explained by a side reaction involving chemical cross-linking of the of nanogel chains with bis-activated FA. Alternatively, swelling may be hindered by association of the FA moieties into multimers owing to Hoogsteen-type hydrogen bonds and stacking interactions[16]. …”
Section: Resultsmentioning
confidence: 99%
“…500 MHz 1 H -NMR spectrum of 400 µM AcCoA in D 2 O, pD 7.4, 25°C (room temperature). Fully resolved spectral assignments were made on the basis of previous studies [72] , [73] .…”
Section: Supporting Informationmentioning
confidence: 99%